Evaluation Study of Post-Stage II Blocks 1970 - Planning Commission (Planning Commission, 1970)
The Community Development programme was initiated. with" the primary objective of involving community participation as supplementary to Government efforts in improving the special and. economic conditions of the rural people. The programme was initiated in 55 Community Project are as all over India on aid October, 1952. Later in 1953, National Extension Service (NES) blocks were introduced. All new areas selected for development were to continue for. 3 years as N.E.S. blocks with a budget provision of Rs. 4.5 lakhs per block.
Programme Evaluation Organisation Planning Commission Government of India
Programme Evaluation Organisation Planning Commission Government of India